Platinum Nanoparticles Decorated IrO2@MWCNT as an Improved Catalyst for Oxygen Evolution Reaction. Issue 29 (11th August 2021) - Cheng, Yaping; Yang, Fan; Gong, Jiafang; Wu, Bohua; Zhang, Zhao; Chu, Jia
Abstract: In this paper, IrO2 nanoparticles supported on multi‐walled carbon nanotubes (MWCNTs) are synthesized via a facile hydrothermal method and calcination process at different temperature. Platinum nanoparticles decorated IrO2 @MWCNT‐400 °C are prepared by chemical reduction method. The influence of MWCNTs and Pt on physicochemical properties and oxygen evolution reaction (OER) activity of IrO2 @MWCNT composites were studied via transmission electron microscope (TEM), X‐ray diffraction (XRD), Raman spectra, thermogravimetric analysis (TGA), X‐ray photoelectron spectroscopic (XPS) and electrochemical methods. Among the samples, Pt/IrO2 @MWCNT‐400 °C exhibits better catalytic activity with an overpotential of 270 mV at the current density of 10 mA cm −2 with a low Tafel slope of 85.1 mV dec −1 . The outstanding OER performance of Pt/IrO2 @MWCNT‐400 °C is ascribed to the introduction of the MWCNTs, which can not only act as a support to prevent agglomeration of IrO2 nanoparticles that produces high surface area of catalytic sites, but also facilitates electron transfer between IrO2 nanoparticles and MWCNTs. On the other hand, the Pt optimizes electronic structure for excellent electrocatalytic performance. Therefore, the Pt/IrO2 @MWCNT‐400 °C catalyst is a good choice for application in OER. Abstract : Platinum nanoparticles decorated IrO2 @MWCNT‐400°C are prepared by chemical reduction method. The superior electrocatalytic activity may be attributed to the MWCNTs prevent agglomeration of IrO2 which produces high surface area of catalytic sites and MWCNTs facilitates electron transfer rate and improves the migration of electrolytes. Furthermore, Pt optimizes electronic structure for excellent electrocatalytic performance.